Understanding The Influence from Electronic Service Quality of Boarding House Website on Customer Satisfaction and Purchase Intention - Fajri, Aulya Husna; Qastharin, Annisa Rahmani (Proceedings International Conference on Education Innovation and Social Science, 2023)
In Indonesia, there are various options for temporary housing available to migrating students, including boarding houses, dormitories, rentals, and apartments. However, numerous obstacles are faced in finding such a limited time to look for boarding houses, availability issues, or unmet expectations. Teman Survei is present as a business that provides a boarding house website to overcome the problem. Unfortunately, the quality of service at Teman Survei is not optimal, resulting in customer dissatisfaction and not continuing to pay. The goal of this study is to better understand the factors of electronic services quality that have an influence on consumer satisfaction and purchase intent. This study also tries to determine the factors most influential on customer satisfaction and purchase intention. Partial Least Square-Structural Equation Modeling, a quantitative technique, was utilized to test the study model using data from 237 users of a boarding house website in Bandung. The outcome demonstrates that customer satisfaction and purchase intention are positively influenced by each of the five elements of electronic service quality: website design, reliability, responsiveness, trust, and personalization.